The bean trees : a novel - Kingsolver, Barbara (New York : HarperCollins Publishers, 1989)
Taylor, a poor Kentuckian making her way west with an abandoned baby girl, stops in Tucson where she finds friends and discovers resources in apparently empty places.
Keywords: AUTOMOBILE TRAVEL